Imported construction materials and techniques in 19th century Ottoman architecture - Yergun, Uzay; Ciftci, Aynur (CRC PRESS-TAYLOR & FRANCIS GROUP, 2008)
European societies created the model for the modernization period that began in the Ottoman state in the eighteenth century and continued during the so-called westernization period Of the nineteenth century. The construction of new types of buildings such as military buildings, western style palaces turned into a reform movement which took western architecture as its model. Due to its conservative structure, the Ottoman State could not completely subscribe to the intellectual movements in the west so it remained tied to the industrial goods that Europe manufactured. For this, after the first quarter of the nineteenth century solid bricks. tiles, metal beams and similar building materials were imported from countries like Britain, France, Belgium. Italy Germany and Austria. Many buildings of the period that remain have been registered as essential cultural assets have faced various problems. The interventions undertaken have damaged construction techniques and the originality of the imported materials.
Keywords: Architecture; Construction & Building Technology; Engineering